Blood gases, biochemistry and haematology of Galápagos marine iguanas (Amblyrhynchus cristatus). (24th July 2015) - Lewbart, Gregory A.; Hirschfeld, Maximilian; Brothers, J. Roger; Muñoz-Pérez, Juan Pablo; Denkinger, Judith; Vinueza, Luis; García, Juan; Lohmann, Kenneth J.
Abstract : The marine iguana is an iconic lizard endemic only to the Galápagos Islands of Ecuador, but surprisingly little information exists on baseline health parameters for this species. The values reported in this study provide baseline data that may be useful in comparisons among populations and in detecting changes in health status among marine iguanas affected by natural disturbances or anthropogenic threats. Abstract : The marine iguana, Amblyrhynchus cristatus, is an iconic lizard endemic to the Galápagos Islands of Ecuador, but surprisingly little information exists on baseline health parameters for this species. We analysed blood samples drawn from 35 marine iguanas captured at three locations on San Cristóbal Island. A portable blood analyser (iSTAT) was used to obtain near-immediate field results for pH, lactate, partial pressure of O2, partial pressure of CO2, bicarbonate (HCO3 − ), percentage O2 saturation, haematocrit, haemoglobin, sodium, potassium, ionized calcium and glucose. Parameter values affected by temperature were auto-corrected by the iSTAT. Standard laboratory haematology techniques were employed for differential white blood cell counts and haematocrit determination; resulting values were also compared with the haematocrit values generated by the iSTAT. Body temperature, heart rate, respiratory rate and body measurements were also recorded. Body length was positively correlated with several blood chemistry values (HCO3 − and glucose) and two haematology parameters (haemoglobin and manually determined haematocrit). A notable finding was the unusually high blood sodium level; the mean value of 178 mg/dl is among the highest known for any reptile. This value is likely to be a conservative estimate because some samples exceeded the maximal value the iSTAT can detect. For haematocrit determination, the iSTAT blood analyser yielded results significantly lower than those obtained with high-speed centrifugation. The values reported in this study provide baseline data that may be useful in comparisons among populations and in detecting changes in health status among marine iguanas affected by natural disturbances or anthropogenic threats. The findings might also be helpful in future efforts to demonstrate associations between specific biochemical parameters and disease.